UNRAVELLING ORNITHOPOD DIVERSITY IN THE LATE JURASSIC COASTAL ECOSYSTEMS OF EASTERN IBERIA (SPAIN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
Ornithopod osteological fossils from the Upper Jurassic of Europe are relatively scarce and often fragmentary compared to those of other dinosaurian groups. Recent discoveries, particularly from the Iberian Peninsula, have increased our understanding of the diversity of these dinosaurs, although much remains poorly understood. This study reports new ornithopod fossils from several sites in the provinces of Valencia and Teruel (Spain). Geologically, all the sites are located within the South Iberian Basin in the Villar del Arzobispo Formation (upper Kimmeridgian–Tithonian). These fossils represent almost half of the ornithopod discoveries in the region. Their systematic study reveals, for the first time, the presence of dryosaurids and small-sized ankylopollexians, while further confirming the presence of large-sized ankylopollexians. These findings significantly increase the known diversity of ornithopods in the Upper Jurassic of eastern Iberia. Notably, small-sized ankylopollexians may have been among  the potential trackmakers of the enigmatic small quadrupedal ornithopod tracks reported from this region. The coexistence of at least three distinct iguanodontian taxa suggests niche partitioning and a high level of ecological complexity within the herbivorous dinosaurian communities of the coastal ecosystems in eastern Iberia during the Late Jurassic, a pattern likely widespread across the Iberian landmass during this epoch.
Keywords: Dinosauria; Ornithopoda; Dryosauridae; Ankylopollexia; Villar del Arzobispo Formation; systematics; biodiversity; palaeoecology.